Evaluation of Gallbladder Motilityin Patients With Functional Gallbladder Disorder - Awami, Salem (Al-Mukhtar Journal of Sciences, 2018)
Rome IV defines Functional gastrointestinal disorders (FGID) as disorders of gut-brain interaction. It is a group of disorders classified by gastrointestinal symptoms related to any combination of the following: motility disturbance, visceral hypersensitivity, altered mucosal and immune function, altered gut microbiota, and altered central nervous system processing. Patients with Gallbladder Functional disorder (GBFD) may have abnormal gastric emptying and colonic transit, suggesting a possible generalized gastrointestinal motility disorder. The presentation of functional gallbladder disorder mimics classic symptoms of biliary pain, 27 patients and 27 healthy volunteers (7 males and 20 females) in each group, age between 21 and 48 years were included into the study, and diagnosis of functional gallbladder disorder was based on Rome III criteria. All patients were given a standard test fatty meal, and Gallbladder volume was calculated manually by using the ellipsoid formula (Dodd’s formula). The pre-meal and post-meal gallbladder volumes and ejection fraction (EF) of the gallbladder (GB) were estimated. The patients and control groups were compared for age, gender, and body mass index. The body mass index in our control and patients was high indicating a prevalence of overweight in both groups. This study demonstrated that fatty meal ultrasound is a cheap, easy to handle, and physiologic. GBFD patients have decreased emptying of gallbladder compared to healthy subjects. GBFD should be considered in patients presented with recurrent right upper quadrant abdominal pain, decreased emptying of gallbladder in the absence of visualized gallstones on abdominal ultrasound, and meeting the Rome III criteria